Reliability-based topology optimization of bridge structures using first and second order reliability methods - Meysam Johari (Iranian Society of Structrual Engineering (ISSE), 2017)
Reliability-based topology optimization (RBTO) results in an optimal topology satisfying given constraints with consideration of uncertainties in the variables. Due to inherent uncertainties, including external loading, material properties, and the quality of construction, prototypes and products may not satisfy the essential functions required. In RBTO, each of these uncertain parameters are treated as random variables and reliability constraints are used in the formulation of the topology optimization problem to obtain a more reliable structure. In this article, RBTO was applied to obtain reliable topologies for two bridge structures using the Solid Isotropic Microstructure with Penalization (SIMP). The first and second order reliability methods are used as reliability analysis methods to take into account the uncertainties of the load, Young's modulus and thickness. It was found that in optimal topologies obtained by RBTO, the corresponding compliance values are higher than values obtained by deterministic topology optimization (DTO) and increase the number of uncertain parameters which results in softer structures with higher compliances.